Elaboration, characterization, and probiotic viability of synbiotic non-dairy drink based on coconut - Paulo Cezar da Cunha Júnior; Lorena de Sá de Oliveira; Jaqueline Costa Blanco; Mariá Toledo de Carvalho Silva; Sandra Guadalupe Lagunes Gálvez; Amauri Rosenthal; Elisa Helena da Rocha Ferreira (Ciência Rural, 2022)
ABSTRACT: Coconut is a fruit grown in more than 80 countries owing to its outstanding nutritional and biological value and it is an important crop for the food industry” por “Coconut is a fruit grown in more than 80 countries and owing to its outstanding nutritional and biological value and it is an important crop for the food industry. Thus, developing new coconut-based products is attractive to explore the benefits provided by microorganisms and improve the nutritional and bioactive composition of coconut products, such as by preparing fermented beverages. This study developed and characterize a drink based on dry coconut with the prebiotic fructooligosaccharide fermented by the probiotic Lactobacillus casei. The drink was formulated, filtered, fermented, matured, and stored under refrigeration (4 °C) for 28 days; it was evaluated for its physical, chemical, antioxidant, and microbiological characteristics. Compared to the standard non-fermented sample during storage, the fermented drink showed significant variations (P < 0.05) in instrumental color, acidity, and pH, while changes in soluble solids and stability index were observed after 7 days of storage. Regarding the chemical composition, all parameters varied significantly after fermentation. The total phenolic compound content and antioxidant capacity increased significantly after fermentation. Significant reductions were observed (P < 0.05) in the viability of Lactobacillus casei after exposure to gastrointestinal tract conditions, with the following counts (in log CFU mL-1) after 0 and 28 days of storage: - initial: 9.23 ± 0.04 and 9.05 ± 0.12; after the gastric phase: 6.21 ± 0.09 and 5.90 ± 0.01; and after the intestinal phase: 4.59 ± 0.33 and 4.75 ± 0.23, respectively.